New N-triaryl-substituted polyamides materials as light Emitters for semiconductors applications - obead, Kawther ayad; Rashid, Azhar Kamil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this work, new di-acid monomers 4, 4â€™-di-carboxillic-2â€-chloro-4â€- nitro triphenylamine (Di-CO2H-1), 4, 4â€™- di-carboxylic -2â€,4â€,6â€-trichloro-triphenylamine (Di-CO2H-2) were synthesized by reaction of p-cyanobenzofluride with two aromatic amines (2-chloro 4-nitro aniline and 2,4,6-trichloro aniline by aromatic nucleophilc substitution method to produce two di cyano intermediates compounds 4, 4â€™-Dicyano-2â€-chloro-4â€- nitro triphenylamine (Di-CN1) and 4, 4â€™-dicyano-2â€,4â€,6â€-trichloro-triphenylamine (Di-CN2) which form final di-carboxylic monomers after alkaline hydrolysis. Finally, these monomers react with two different aromatic di amines, phenylene diamins and benzidine respectively via polycondensation reaction to form final polyamides 2â€-chloro-4â€- nitro -triphenylamine-4, 4'-polyphenylbenzamide (Pa), 2â€,4â€,6â€-trichloro-triphenylamine -4,4'-polyphenylbenzamide (Pb), 2â€-chloro-4â€- nitro triphenylamine-4,4'- polyphenylbiphenylamide (Pc), 2â€,4â€, 6â€-trichloro-triphenylamine-4,4â€™- polyphenylbiphenylamide (Pd).The chemical structure of these polymers characterized by FTIR and NMR techniques. The polyamides showed a good thermal stability with height glass transition temperatures (Tg).Thin casting films of these polyamides in cyclic voltammetry (C.V) on glass substrate of iridium-tin oxide (ITO) as working electrode in dry CH3CN solvent contains 0.1 M of tetrabutylantimoneperchlorate (TBAP) as an electrolyte gave one redox wave.